The equality used is Subtraction property of equality
Option A is correct
Step-by-step explanation:
We need to identify which option best explains or justifies Step 1.
Step 1 is: ![-c = ax^2 + bx](https://tex.z-dn.net/?f=-c%20%3D%20ax%5E2%20%2B%20bx)
The given equation is: ![0 = ax^2 + bx + c](https://tex.z-dn.net/?f=0%20%3D%20ax%5E2%20%2B%20bx%20%2B%20c)
To get the equation for step 1 we need to subtract c on both sides of equation i.e using subtraction property of equality
![0-c = ax^2 + bx + c-c](https://tex.z-dn.net/?f=0-c%20%3D%20ax%5E2%20%2B%20bx%20%2B%20c-c)
![-c = ax^2 + bx](https://tex.z-dn.net/?f=-c%20%3D%20ax%5E2%20%2B%20bx%20)
So, The equality used is Subtraction property of equality
Option A is correct.
Keywords: Solving Quadratic Equations
Learn more about Solving Quadratic Equations at:
#learnwithBrainly
Answer:
2,880
Step-by-step explanation:
P + 60N = x
1500 + 60(23) = x
1500 + 1380 = x
2880 = x
Answer:
21:24 24:64
Step-by-step explanation:
Ur mouse is covering the number but yea
Answer:
1 question : 0.89 I think.